THE RISE OF INNOVATION IN INDIA - Mani, Sunil (SCHOOL SCIENCE, 2010)
In recent years, there has been much discussion in expert circles and the popular press about the rise of innovation in India. In the following extract from the chapter on India in the UNESCO Science Report2010, we explore the reasons behind this success story and the challenges that remain.